2014
DOI: 10.1155/2014/463152
|View full text |Cite
|
Sign up to set email alerts
|

[11C]-Methionine Positron Emission Tomography in the Postoperative Imaging and Followup of Patients with Primary and Recurrent Gliomas

Abstract: We investigated the sensitivity and specificity of [11C]-methionine positron emission tomography ([11C]-MET PET) in the management of glioma patients. We retrospectively analysed data from 53 patients with primary gliomas (16 low grade astrocytomas, 15 anaplastic astrocytomas and 22 glioblastomas) and Karnofsky Performance Status (KPS) > 70. Patients underwent [11C]-MET PET scans (N = 249) and parallel contrast-enhanced MRI (N = 193) and/or CT (N = 113) controls. In low grade glioma patients, MRI or CT finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 21 publications
0
10
0
3
Order By: Relevance
“…In addition, [ 11 C]-MET-PET imaging increases the sensitivity of CT and/or MRI scans up to 97% in the post-surgical evaluation and even in the assessment during adjuvant therapy. 69 These aspects lend important information regarding the definition of target volume and margins. CTV margins of Gd-enhancing areas and suspect areas in T2 sequences differ considerably from those by amino acid PET.…”
Section: Imaging Implications In Neurosurgerymentioning
confidence: 99%
“…In addition, [ 11 C]-MET-PET imaging increases the sensitivity of CT and/or MRI scans up to 97% in the post-surgical evaluation and even in the assessment during adjuvant therapy. 69 These aspects lend important information regarding the definition of target volume and margins. CTV margins of Gd-enhancing areas and suspect areas in T2 sequences differ considerably from those by amino acid PET.…”
Section: Imaging Implications In Neurosurgerymentioning
confidence: 99%
“…(i.e better signal to noise ratio) Methionine is involved in protein synthesis, energy production. I t is clear that MET is a powerful diagnostic tool for the detection of primary [61][62][63][64][65][66] and recurrent [42,52,62,[66][67][68][69][70] glioma, as well as having some benefit in prediction of survival. [30,55,[71][72][73][74] Numerous investigations have been performed comparing the diagnostic accuracy of FDG and MET, with reported findings clearly showing the superiority of MET in detection [21,30,75] and grading [30,31] of primary glioma.…”
Section: [ 11 C]-l-methionine (Met)mentioning
confidence: 99%
“…Ceyssens et al [74] and Moulin-Romsee et al [79] reported that MET could not differentiate between glioma grades. However, Singhal et al [30] found that MET could discriminate between high and low-grade gliomas and Miyake et al [31] and Santoni et al [62] found the tracer could discriminate between grades II and IV and grades II, III and IV, respectively.…”
Section: [ 11 C]-l-methionine (Met)mentioning
confidence: 99%
See 1 more Smart Citation
“…Метионин, меченный углеродом-11 ( 11 С), стал таким РФП. Полученные в ходе дальнейших сравнительных исследований на большой группе пациентов (n=102) результаты продемонстрировали диагностические преимущества 11 С-метионина над 18 F-ФДГ в оценке степени злокачественности глиальных новообразований [3,4].…”
unclassified